1953
DOI: 10.1002/j.2333-8504.1953.tb00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relative Movement Test by a Method of Individual Interviews

Abstract: The purpose of this study was to analyze performance on the Relative Movement Test, a part of the U. S. Navy Officer Classification Battery, in order to obtain a better understanding of what the test measures. More adequate information about the test should be of value in indicating how more effective measures may be produced for use by the Navy in selection and classification of personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1955
1955
1991
1991

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…If it is supposed, for example, that a test measures mathematical competence, and yet observation of students' errors shows that erroneous reading of the question is common, the implications of a low score are altered. Lucas in this way showed that the Navy Relative Movement Test, an aptitude test, actually involved two different abilities: spatial visualization and mathematical reasoning (39).…”
Section: Validation Proceduresmentioning
confidence: 99%
“…If it is supposed, for example, that a test measures mathematical competence, and yet observation of students' errors shows that erroneous reading of the question is common, the implications of a low score are altered. Lucas in this way showed that the Navy Relative Movement Test, an aptitude test, actually involved two different abilities: spatial visualization and mathematical reasoning (39).…”
Section: Validation Proceduresmentioning
confidence: 99%
“…Following the early identification of spatial factors, attempts to develop "pure factor" tests began. However, complex and nonuniform factor structures continued to characterize the spatial performance of even the relatively homogeneous groups of young men tested (Barratt, 1953;Koussy, 1935;Lucas, 1953;Michael, Zimmerman, & Guilford, 1950;Myers, 1958). Researchers began exploring solution strategies in order to account for the complexity of the observed factor structures (Barratt, 1953;Koussy, 1935).…”
mentioning
confidence: 99%